Does GPAQ exhibit a higher correlation with the maximum oxygen capacity than IPAQ among young adults? - Gilang Fachri Maulana; Novita Intan Arovah (UIR Press, 2021)
International Physical Activity Questionnaire (IPAQ) and the Global Physical Activity Questionnaire (GPAQ) are the two most widely used to measure physical activity (PA). Yet, their convergent validation with the maximum oxygen capacity (VO2Max) among Indonesian young adults is unknown. This study compared physical activity (PA) assessments using IPAQ and GPAQ and their correlations with the maximal oxygen capacity (VO2Max) in the young adult population. This study was a cross-sectional descriptive study on 63 Sports Science students (84.13% Male age ranged 18-22 years). PA was measured using both the GPAQ and IPAQ to calculate the total PA and PA in each domain (i.e. work-related, transport-related, and leisure). One additional domain which was household-related was assessed exclusively for the IPAQ based on the scoring guideline. The VO2Max was measured using a standard equation based on participants’ performance on a 1-mile run. Paired sample t-test was conducted to compare total PA based on GPAQ and IPAQ while the Wilcoxon sign rank test was conducted to compare GPAQ and IPAQ domains. Pearson or Spearman correlation test assessed the correlations among the VO2Max, total PA, and PA on each GPAQ’s and IPAQ domain. No significant difference in the total PA per week between IPAQ and GPAQ was found. Significant differences, however, were found in work and transport domains, but not in the leisure domains. A moderate correlation among GPAQ and IPAQ (r=0.56, p=0.01), a moderate correlation between GPAQ and VO2Max (r=0.41, p= 0.01) but a weak correlation between IPAQ dan VO2Max (r=0.25, p<0.05) were demonstrated. While, this study has indicated convergent validity of both GPAQ and IPAQ, GPAQ has a higher correlation with VO2Max compared to the IPAQ. Therefore, GPAQ is more recommended to be used to measure PA levels among Indonesian young adults compared to IPAQ.